The genus guerrerostrongylus (Nematoda: Heligmonellidae) in cricetid rodents from the atlantic rain forest of misiones, Argentina: Emended description of guerrerostrongylus zetta (Travassos, 1937) and description of a new species - Digiani, Maria Celina (2012)
Two species of Guerrerostrongylus Sutton and Durette-Desset, 1991, are reported in cricetid rodents from the Atlantic rain forest of Misiones, Argentina. Guerrerostrongylus zetta (Travassos, 1937) is redescribed on the basis of material collected from Oligoryzomys nigripes from Argentina and material loaned by CHIOC from Brazil. It is characterized by a synlophe with about 4045 (3548) well-developed cuticular ridges, caudal bursa with long rays 6 and dorsal ray divided at mid-length, and well-sclerotized spicules with marked twisting. It was found with a prevalence of 100 in O. nigripes (14 hosts examined); however, it was not found in its type host Nectomys squamipes (4 hosts examined). Guerrerostrongylus ulysi n. sp., which is described from Sooretamys angouya, differs from the remaining species in the genus mainly by a synlophe with a strong reduction of the cuticular ridges and struts on the right side, and by a heart-shaped caudal bursa, with short rays 6 and a dorsal ray divided distally. It was found with a prevalence of 100 in 5 hosts examined. © American Society of Parasitologists 2012.